Adsorption of Ni(II) on spent coffee and coffee husk based activated carbon. Issue 1 (February 2018) - Hernández Rodiguez, Mónica; Yperman, Jan; Carleer, Robert; Maggen, Jens; Dadi, Dessalegn; Gryglewicz, Grazyna; Van der Bruggen, Bart; Falcón Hernández, José; Otero Calvis, Alexis
Abstract: Adsorption of Ni(II) on low cost activated carbon (AC) from spent coffee (SAC) and coffee husk (HAC) has been studied. Porous textures of adsorbents were characterized by N2 and CO2 sorption measurements. Batch adsorption experiments were performed as a function of adsorbent dose, Ni(II)-concentration and pH. Adsorption of Ni(II) was evaluated using different adsorption isotherm models (Langmuir, Freundlich, Monolayer Model for Single-Compound Adsorption and Dubinin – Radushkevich) and thermodynamics and kinetics parameters were determined. Both adsorbents show high affinity for Ni(II), however both the surface area and the pore size of the ACs do not seem to be the determining factor in the adsorption process. These ACs are microporous in nature. In contrast, the higher oxygen amount associated to the mineral matter as K2 O and carbon functionalities corresponding with OH in HAC are determining for the Ni-ion adsorption process and multi-ion anchorage mechanism. In addition, the exchange of potassium present in the ACs improves the Ni(II) adsorption process. Thermodynamics and kinetics evidence a fast and endothermic adsorption process. The maximum adsorption capacity using the Langmuir isotherm model was found to be 57.14 mg/g and 51.91 mg/g for HAC and SAC, respectively. The sorption efficiency was higher for HAC as adsorbent. At low concentrations of Ni(II) (30 mg/L) and higher temperatures (308–328 K), removals >94% were measured for HAC, achieving safe discharge concentration values.